Folding and unfolding movements in a [2]pseudorotaxane - Suresh, Moorthy; Mandal, Amal Kumar; Kesharwani, Manoj K.; Adarsh, N. N.; Ganguly, Bishwajit; Kanaparthi, Ravi Kumar; Samanta, Anunay; Das, Amitava (Journal of Organic Chemistry, 2011)
A new dibenzo[24]crown-8 derivative (1) was synthesized and functionalized with aromatic moieties such as naphthalene and coumarin units. These two fluorophores are known to form an effective FRET (Forster resonance energy transfer) pair, and this formed the basis for the design of this host crown ether derivative. Results of the steady-state and time-resolved fluorescence studies confirmed the resonance energy transfer between the donor naphthalene moiety and acceptor coumarin fragment, while NMR spectra and computational studies support a folded conformation for the uncomplexed crown ether 1. This was found to form an inclusion complex, a [2]pseudorotaxane type with imidazolium ion derivatives as the guest molecules with varying alkyl chain lengths ([C4mim]+ or [C10mim]+). The host crown ether (1) tends to adopt an open conformation on formation of the interwoven inclusion complex (1·[C4mim]+ or 1·[C10mim]+). This change in conformation, from the folded to a open one, was predicted by computational as well as 1H NMR studies and was confirmed by single crystal X-ray structure for one (1·[C4mim]+) of the two inclusion complexes. The increase in the effective distance between the naphthalene and coumarin moieties in the open conformation of these inclusion complexes was also supported by the decrease in the effective FRET process that was operational between naphthalene and coumarin moieties in the free molecule (1). Importantly, this inclusion complex formation was found to be reversible, and in the presence of a stronger base/polar solvent, such as triethyl amine/DMSO, the deprotonation/effective solvation of the cationic imidizolium ions ([C4mim]+ or [C10mim]+) resulted in decomplexation or dethreading with restoration of the original emission spectra for 1, which signifies the subsequent increase in the FRET process. Thus we could demonstrate that a molecular folding-unfolding type of movement in the crown ether derivative could be induced by chemical input as an imidazolium ion.

First demonstration of two-step FRET in a synthetic supramolecular assembly - Suresh, Moorthy; Mandal, Amal Kumar; Suresh, E.; Das, Amitava (Chemical Science, 2013)
We report a trichromophoric pseudorotaxane (3NPC) that demonstrates a two-step FRET-based relay comprising of primary donor–primary acceptor/secondary donor–secondary acceptor pairs. To achieve this, naphthalene (1) and coumarin (3) were used as the primary donor and secondary acceptor, respectively; while pyrene (2 or T) unit, having spectral overlap with both 1 and 3, was used as the primary acceptor as well as the secondary donor. Results of time resolved and steady-state emission studies reveal that sequential resonance energy transfer (FRET 1 → 2 → 3) and direct resonance energy transfer (FRET 1 → 3) processes are operational simultaneously. In the sequential energy transfer process (1 → 2 → 3) of the triad system, pyrene acts as a transmitter and makes the whole supramolecular assembly behave as a linear energy transferring wire. Sensitised emission of the coumarin moiety, i.e. the secondary and eventual final acceptor, offers the possibility of evaluating the performance of this linear trichromophoric system by one and two-step FRET mechanisms. Formation of an interwoven complex between the host (NCC24O8) and the guest (T) components, utilizing various non-bonding interactions (intercomponent [N+–H⋯O], [C–H⋯O] and π–π stacking interactions) has been confirmed by 1H NMR studies in solution and a single crystal X-structural study in the solid state. The formation constant (Kf = 2.31 × 103 M−1) for the [2]pseudorotaxane was evaluated using isothermal titration calorimetric studies. The complex gives rise to the first crystal structure of a self-assembled [2]pseudorotaxane that demonstrates sequential two-step FRET based energy transfer in a self-assembled triad that is held in an assembly through non-covalent interactions, such as hydrogen bonding and π–π stacking.

Fluorescent probe for specific detection of cysteine in the lipid dense region of cells - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Gonnade, Rajesh G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new cysteine (Cys) specific chemodosimetric reagent (ER-F) is used in imaging of endogenous Cys localized in the lipid dense region of the live Hct116 cells and the release of Cys within HepG2 cells from a drug following a biochemical transformation. A silica surface, modified with ER-F, could be used for quantitative estimation of Cys present in aqueous solution (pH 7.2) and in a human blood plasma (HBP).

Fluorescent probes for the detection of cyanide ions in aqueous medium: cellular uptake and assay for beta-glucosidase and hydroxynitrile lyase - Agarwalla, Hridesh; Gangopadhyay, Monalisa; Sharma, Dharmendar Kumar; Basu, Santanu Kumar; Jadhav, Sameer; Chowdhury, Arindam; Das, Amitava (Journal of Materials Chemistry B, 2015)
A chemodosimteric reagent (1) for the efficient detection of cyanide species (CN- and/or HCN) in aq. medium as well as under physiological conditions has been described. Selective reaction of the cyanide species with this reagent in the presence of all common interfering anions, amino acids and glutathione (GSH) led to the generation of the corresponding cyanohydrin derivative. The formation of the cyanohydrin derivative of the probe is associated with a visually detectable change in solution fluorescence in aq. buffer medium with 1.9 mu M NaCN, the threshold limit set by WHO for the safe drinking water and this makes this fluorogenic sensor an ideal candidate for in-field applications. An apparent switch on the luminescence response, ultralow detection limit, low response time, cell membrane permeability and insignificant toxicity are key features of a probe molecule, which gives it a distinct edge over previously reported chemodosimetric reagents for the detection of cyanide species (CN- or HCN) in an aqueous environment. This methodology could be used for developing a generalized and efficient fluorescence-based assay for crucial enzymes like beta-glucosidase and hydroxynitrile lyase. Furthermore, spectrally-resolved fluorescence microscopy measurements on single-cells revealed that this sensor molecule could also be used for imaging the cellular uptake of cyanide species from aq. solution contaminated with NaCN. Our results confirmed that statistical analysis of integrated intensity and transition energy obtained from the emission spectra collected over various microscopic sub-cellular regions can potentially be used to discriminate the effects of local cellular environments and that due to cyanide detection.

FRET-based probe for monitoring pH changes in lipid-dense region of Hct116 cells - Reddy, Upendar G.; Anila, H. A.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Organic Letters, 2015)
A rhodamine conjugate (L) with a pseudo Stokes shift of 165 nm is used for probing changes in solution pH under physiological conditions. This reagent is found to be nontoxic, and the luminescence response could be used for imaging changes in endogenous pH induced by dexamethanose (DMT) in the endoplasmic reticulum.

Fluorescent probe for bisulfite ions: its application to two-photon tissue imaging - Agarwalla, Hridesh; Pal, Suman; Paul, Anirban; Jun, Yong Woong; Bae, Juryang; Ahn, Kyo Han; Srivastava, Divesh N.; Das, Amitava (Journal of Materials Chemistry B, 2016)
A benzoxazinone based fluorescent probe for the specific and efficient detection of bisulfite ions in aqueous medium is described. The probe formed a bisulfite/sulphite adduct with an associated turn-on fluorescence response in the red wavelength region. No interference was observed in the detection process from all possible competing anions and molecules, including cyanide ion, cysteine, homocysteine and glutathione. In addition, the probe showed a fast response time, low detection limit, and cell membrane permeability. Furthermore, the probe was two-photon excitable, enabling imaging of endogenous bisulfite ions in HeLa cells as well as in deep tissues from different organs of mouse.

Fluorescent chemodosimeter for quantification of Cystathionine-y-synthase activity in plant extracts and imaging of endogenous biothiols - Agarwalla, Hridesh; Hoskere, Anila A.; Ali, Firoj; Pradhan, Swaraj Rashmi; Ganguly, Bishwajit; Pramanik, Sumit kumar; Das, Amitava (Chemical Communications, 2018)
A new reagent for quantification of CgS in plant extracts using a generalized methodology suitable for recognition of homocysteine (Hcy) with luminescence ON response.

Fluorogenic BODIPY molecular rotor as an apoptosis marker - Ashokkumar, Pichandi; Ashoka, Anila Hoskere; Collot, Mayeul; Das, Amitava; Klymchenko, Andrey S. (Chemical Communications, 2019)
Based on a BODIPY molecular rotor and a zinc-dipicolylamine receptor, we designed a fluorogenic probe for the detection of apoptosis. Being poorly emissive in solution and with healthy cells, it selectively binds phosphatidylserine of early apoptotic cells and internalizes into late apoptotic cells, lighting up its green fluorescence.